Effect of cations and anions on flocculation of dispersive clayey soils - Abbaslou, Hanie (Heliyon, 2020)
Dispersivity of clay soils is one of the most important issues that should be considered in civil engineering projects. Dispersive soils are clay soils that are easily washed in water with low concentrations of salt; these clay soils usually contain high levels of sodium ions in their adsorption cation sites. Kaolin, sepiolite (fibrous clay), and bentonite soils are among the most important and useful industrial materials. Therefore, in this study, these three clay soils were selected to investigate dispersivity potential by adding 4% of dispersive materials (Sodium hexametaphosphate) and performing shear strength, crumb, double hydrometer, pinhole tests, and chemical experiments. Results indicated a change in the Sodium Adsorption Ratio (SAR) in the following order: kaolin > sepiolite > bentonite. Stabilization practices using chemical methods were done after performing soil divergence with sodium hexametaphosphate. CaCl(2), CaSO(4), AlCl(3), and Al(2) (SO(4))(3) were used for chemical stabilization to assess the effect of ion valence on soil improvement parameters. Results obtained for chemical properties showed that, stabilization potential was in the following order: kaolin > sepiolite > bentonite; meaning that clay soils with lower cation exchange capacity have more remediation potential and are more susceptible to dispersion. The role of calcium and aluminum cations was prominent in improving mechanical and dispersivity properties, respectively. In general, further dispersion potential of clays in the same Na(+) concentration was found to be related to a decrease in the cation exchange capacity, specific surface area, and plastic index. Soil dispersion was directly associated with diffuse double layer and electrostatic forces while; soil strength parameters were mainly dependent on cementation and connection of soil particles to each other. Consequently, it was observed that, clay soils with suitable engineering properties (higher strength and compaction or lower Atterberg limits) are more sensitive to dispersion compared to other types of clay with higher CEC and plasticity values.